Treatment of Invasive Brain Tumors Using a Chain-like Nanoparticle - Peiris, Pubudu M; Abramowski, Aaron; Mcginnity, James; Doolittle, Elizabeth; Toy, Randall; Gopalakrishnan, Ramamurthy; Shah, Shruti; Bauer, Lisa; Ghaghada, Ketan B; Hoimes, Christopher; Brady-Kalnay, Susann M; Basilion, James P; et al. (Cancer research (Chicago, Ill.), 2015)
Glioblastoma multiforme is generally recalcitrant to current surgical and local radiotherapeutic approaches. Moreover, systemic chemotherapeutic approaches are impeded by the blood-tumor barrier. To circumvent limitations in the latter area, we developed a multicomponent, chain-like nanoparticle that can penetrate brain tumors, composed of three iron oxide nanospheres and one drug-loaded liposome linked chemically into a linear chain-like assembly. Unlike traditional small-molecule drugs or spherical nanotherapeutics, this oblong-shaped, flexible nanochain particle possessed a unique ability to gain access to and accumulate at glioma sites. Vascular targeting of nanochains to the αvβ3 integrin receptor resulted in a 18.6-fold greater drug dose administered to brain tumors than standard chemotherapy. By 2 hours after injection, when nanochains had exited the blood stream and docked at vascular beds in the brain, the application of an external low-power radiofrequency field was sufficient to remotely trigger rapid drug release. This effect was produced by mechanically induced defects in the liposomal membrane caused by the oscillation of the iron oxide portion of the nanochain. In vivo efficacy studies conducted in two different mouse orthotopic models of glioblastoma illustrated how enhanced targeting by the nanochain facilitates widespread site-specific drug delivery. Our findings offer preclinical proof-of-concept for a broadly improved method for glioblastoma treatment.